Internalisasi Nilai Pendidikan Akhlak pada Mahasiswa Generasi Z Malang Raya - Fauziah, Fauziah; Winarti, Endah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
Malang Raya students who represent Generation Z essentially have the potential to ignore the value of moral education so that it is reflected in their daily behavior. Moral education emphasizes the adaptation process in strengthening the learning process that involves the role of educators in controlling the orientation of students in their attention to the massive use of gadgets and tends to be indifferent to moral education. Therefore, this study aims to measure the internalization of moral education values ​​for Generation Z students in Malang Raya. The research method used is a quantitative approach with a survey research type. The data collected are in the form of responses or information from 202 students at 4 PTKI in Malang Raya. The results of this study indicate that the results of the Kol-Smirnov normality test are 1.005 with a significance of 0.264 where the average value of student internalization is 76.23 which can be categorized as quite good in implementing moral education values ​​in daily life interaction patterns. Thus, the interaction patterns between Generation Z students should be able to present good behavior and interactions.